East Florida records
Diplomatic, military, economic, judicial, legal, and administrative records of the Spanish colonial government of East Florida for the period of its second occupation, 1783-1821. Includes royal orders and decrees, census and other vital records, and records relating to such matters as defense, trade and shipping, surveys, hospitals, native Americans, slaves, and Louisiana. Also includes records pertaining to the earlier Spanish colonial government of East Florida, 1565-1763.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in Spanish and English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hospitals -- Florida; Indians of North America -- Florida; Justice, Administration of -- Florida; Law -- Florida; Recording and registration -- Florida; Shipping -- Florida; Slaves -- Florida; Slavery -- Florida; Florida -- Census; Florida -- Commerce; Florida -- Defenses; Florida -- Economic conditions -- 18th century; Florida -- Economic conditions -- 19th century; Florida -- History -- Spanish colony, 1565-1763.; Florida -- History -- Spanish colony, 1784-1821.; Florida -- History, Military -- 18th century; Florida -- History, Military -- 19th century; Florida -- Politics and government; Florida -- Surveys; Louisiana -- History; New Spain -- Foreign relations; Spain -- Colonies -- America